Titi monkeys combine alarm calls to create probabilistic meaning - Berthet, Mélissa (Sci Adv, 2019)
Previous work suggested that titi monkeys Callicebus nigrifrons combine two alarm calls, the A- and B-calls, to communicate about predator type and location. To explore how listeners process these sequences, we recorded alarm call sequences of six free-ranging groups exposed to terrestrial and aerial predator models, placed on the ground or in the canopy, and used multimodel inference to assess the information encoded in the sequences. We then carried out playback experiments to identify the features used by listeners to react to the available information. Results indicated that information about predator type and location were encoded by the proportion of B-call pairs relative to all call pairs of the sequence (i.e., proportion of BB-grams). The results suggest that the meaning of the sequence is not conveyed in a categorical but probabilistic manner. We discuss the implications of these findings for current theories of animal communication and language evolution.